STRUCTURAL CHANGES OF THE PULMONARY ARTERIES AFTER BALLOON PULMONARY ANGIOPLASTY IN PATIENTS WITH CHRONIC THROMBOEMBOLIC PULMONARY HYPERTENSION - S. Y. Yarovoy; N. M. Danilov; Yu. G. Matchin; I. E. Chazova (Евразийский Кардиологический Журнал)
Aim. To assess the effect of balloon pulmonary angioplasty (BPA) on structural parameters of the pulmonary arteries in inoperable patients with chronic thromboembolic pulmonary hypertension (CTEPH).Materials and methods. The study included 21 patients with an inoperable form of CTEPH. Assessment of clinical and hemodynamic parameters, pulmonary arteries diameters according to angiography, and structural parameters of the pulmonary arteries according to intravascular ultrasound (IVUS) in 11 patients was performed initially, immediately after BPA and after a series of BPA.Results. In total 50 BPA were performed – series of 2.3 ± 1.5 BPA per patient. The observation was carried out for 165 (88; 248) days. After series of BPA there were found out positive changes of clinical and hemodynamic parameters, including functional class, distance in the 6-minute walk test, mean pulmonary artery pressure (mPAP), pulmonary vascular resistance (PVR). According to angiography there was observed a continued dilation of the arteries at the level of segmental arteries and the 1st order branches of subsegmental arteries after the first BPA. According IVUS measurements the greatest changes during the observation period were determined at the 1st and 2d order branches of subsegmental pulmonary arteries – increased outer and inner diameters, vessel lumen area, decreased vascular wall area. A statistical relationship was found out between the diameter of the 1st order branches of subsegmental arteries after BPA and mPAP (r = -0.74, p = 0.006), cardiac output (r = 0.71, p = 0.010), PVR (r = -0, 78, p = 0.003).Conclusion. BPA in inoperable patients with CTEPH leads to a persistent enlargement of the ballooned vessel lumen. In the long term, there is a positive remodeling of the pulmonary arteries with the greatest effect at the level more distal than subsegmental arteries. The diameter of the vessels at this level has a strong correlation with the hemodynamic result of BPA.